ADMINISTRATIVE MANAGEMENT AND EXPORT OF HYDROBIOLOGICAL PRODUCTS IN ARTISANAL FISHERMEN OF SAN ANDRÉS, PISCO-ICA: A CORRELATIONAL ANALYSIS - RUIZ, Mtro. CLEIDY SOFIA FARFAN; PASACHE, Dra. ROSA LUZ GALINDO; HERNÁNDEZ, Mtro. GLADYS YANET DÍAZ; VELARDE, Mtro. JAKSAVIT RACIEL PORTAL; DÁVALOS-ALMEYDA, Dra. MARIA EMILIA; CARDENAS, Mtro. MARIA JOSÉ DEL PILAR CEVALLOS; SALVADOR, Mtro. MARISELA TRILLO (Journal of Posthumanism, 2025)
Objective: To evaluate the administration and procedures for the export of seafood products in the Ica area, recognizing the advantages, disadvantages and areas for improvement, based on the comparison between the results of applied research and the most recent commercial and productive statistics.Method: A descriptive and analytical method was used, supported by the review of specialized literature, the study of applied research on seafood exporting companies in Ica, and the inclusion of updated statistical data from PRODUCE, INEI and SUNAT (2024).Results: The results indicate that business management faces challenges in terms of innovation, collaboration, and diversification, which limits its ability to compete internationally. Extractive fishing focuses mainly on the production of fishmeal and fish oil, reaching 74. 8% by 2024, while aquaculture relies almost entirely on scallop farming, which made up 100% of aquaculture production in the region in 2024. Although regional exports increased by 12. 8%, concentration on production and the limited capacity of companies to adapt represent strategic challenges.Conclusion: Improving administration and diversifying exports are essential aspects to increase the competitiveness of the hydrobiological products sector in Ica. It is suggested to promote public policies and business strategies focused on innovation, added value and sustainability, so that the sector contributes effectively to regional development and achieves a stronger insertion in global markets.